Estimasi Potensi Debit Air Akuifer Menggunakan Metode Geolistrik Tahanan Jenis - Muhammad Zuhdi; Syamsuddin Syamsuddin; Bakti Sukrisna; Teguh Ardianto; Agus Wahid Habiburrohman (Kappa Journal, 2022)
The geoelectric method is a very effective method for subsurface aquifers (water reserves). This method is based on the injection of an electric current from the surface to the earth's body with a certain electrode configuration. The geoelectric method used in this study uses a Schlumberger electrode configuration. Surveys with this method are proven to be able to map the height of the water table at a point in the survey area. In this study, the geoelectric method has been proven to be able to map the potential for water flow discharge in aquifers. From the results of the calculation of the potential for water discharge using the Darcy equation, it is found that the discharge value is around 22.11 liters per second.